KEAWETAN KAYU MANGGA (Mangifera indica) YANG DIAWETKAN DENGAN DAUN SIRSAK (Annona muricata L.) DAN BORAKS TERHADAP SERANGAN RAYAP TANAH - Nurma Safrina Nasution; Diana Ulfah; Henny Arryati (Jurnal Sylva Scienteae, 2020)
The wood needs continue to rise causing the declining supply of wood with durable high grade. Addressing the needs of the wood is currently much used wood from different types of fruits, one of which is the bnayak mango wood is used as a material for furniture where the wood has a low grade durability durable V. This research was held the Wood Chemistry Laboratory of the Faculty of Forestry ULM using natural preservation of soursop leaves and borax chemical preservatives. The size of the wood that used in this research is 25 cm x 5 cm x 2.5 cm. The findings of this research are absorptions, retention, weight loss and degree of damage with a simple Randomized Analysis Design (RAL). Preservation of Mango wood (Mangifera indica) with soursop leaves by using 200 soursop leaves with (6.04% concentration) is the most optimal preservation value of 84.26 kg / m3 while using Borax as preservative with (10% concentration)  has preservation value of 76 , 55 kg / m3. The lowest average degrees of termite attack damage value is the usage of 200 sheets soursop leaves with (6.04% concentration), while the highest average value is The usage of 100 sheets soursop leaves (with 3.04% concentration). The highest average value of Weight loss due to termite attacks is the usage of Borax with 15% concentration, while the lowest is the usage of 200 sheets of soursop leaves (6.04% concentration). Keywords: Mango wood (Mangifera indica); natural preservative of soursop leaves (Annona muricata L.); preservative of borax synthesis